Primary membranous nephropathy: comprehensive review and historical perspective. Issue 1119 (25th January 2019) - Keri, Krishna C; Blumenthal, Samuel; Kulkarni, Varsha; Beck, Laurence; Chongkrairatanakul, Tepsiri
Abstract: Membranous nephropathy (MN) is the most common cause of nephrotic syndrome in non-diabetic Caucasian adults over 40 years of age. It has an estimated incidence of 8–10 cases per 1 million. Fifty per cent of patients diagnosed with primary MN continue to have nephrotic syndrome and 30% of patients may progress to end-stage renal disease over 10 years. Although it was recognised as a distinct clinic-pathological entity in 1940s by immunofluorescence and electron microscopy, the pathogenesis and treatment have become more apparent only in the last decade. Discovery of M-type phospholipase A2 receptor (PLA2R) antibodies and thrombospondin type 1 domain-containing 7A antibodies has given new perspectives in understanding the pathogenesis of the disease process. Anti-PLA2R antibody is the first serologic marker that has promising evidence to be used as a tool to prognosticate the course of the disease. More importantly, therapeutic agents such as rituximab and adrenocorticotropic hormone analogues are the newer therapeutic options that should be considered in the therapy of primary MN.